Toward a Refined Understanding of Cluster Reduction: Phonotactic Innovation and Elision in Bangkalanese Madurese - Azhar, Iqbal Nurul (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This article examines the phenomenon of elision in the vocabulary of the Bangkalan dialect of Madurese, a feature that reveals both systematic regularities and sporadic irregularities in its phonological structure. The investigation addresses the principles underlying elision that occur in a patterned manner as well as those that emerge unpredictably, thus pointing to deeper complexities in the dialect’s phonetic/phonemic system. The data were elicited from two native speakers of the Bangkalan dialect through structured interviews using an instrument originally designed by Nothofer and later refined by Laksono and Savitri (2009). The recordings were transcribed phonetically to facilitate analysis, after which the forms were closely examined to classify their elision status and taxonomy. The analysis identified seven types of elision-based phonological processes: apheresis, syncope, vowel cluster reduction, initial syllable reduction, apocope, final syllable reduction, and double syllable reduction. Among these, syncope emerges as the most influential, contributing to the proliferation of consonant clusters that distinguish Bangkalan Madurese from other dialects. Furthermore, the three reduction processes, initial, final, and double syllable reduction, play a role in shortening lexical items, thereby shaping a vocabulary that is characteristically more compact than that of other Madurese varieties. These findings underscore the interaction between systematic phonological tendencies and irregular developments, positioning Bangkalan Madurese as a dialect that simultaneously preserves, reshapes, and mystifies the broader landscape of Madurese phonology